Underkeel Clearance Reliability Model for Dredged Navigation Channels. Issue 1 (January 2017) - Scully, Brandan M.; Mitchell, Kenneth Ned
This paper presents a reliability measure for selecting marine navigation channel maintenance depth. Resource constraints have resulted in dredging requirements outpacing the funds available to the U.S. Army Corps of Engineers to perform navigation channel maintenance dredging, but navigation managers lack a method to objectively select maintenance depth alternatives to authorized project depths. The reliability of a navigation channel can be determined as the probability that a vessel's net underkeel clearance is greater than or equal to 0. Net underkeel clearance was hindcast from underkeel clearance contributors that include sailing draft, water level, bathymetric elevation, vessel squat, and wave response. This method was tested in Charleston Harbor, South Carolina, with an authorized depth of 45 ft (13.7 m). The harbor includes two-way container, tanker, roll on–roll off, and passenger traffic with maximum drafts exceeding design depth. Vessel squat in transit is calculated on the basis of vessel speed, obtained from Automatic Identification System (AIS) data and a representative block coefficient based on vessel size and type. This study used archival AIS data, bathymetric surveys, observed water level elevations, and information collected by vessel pilots to calculate net underkeel clearance of vessel transits through each dredged location within the harbor in 2011. It was determined that channel reliability ranged from 98.7% to 100%. Channels with 100% reliability had minimum net underkeel clearance between 1.0 ft (0.3 m) and 8.3 ft (2.5 m). The approach provides a potential method to select maintenance depth alternatives to authorized channel depths that may result in maintenance cost savings that arise from avoided dredging and associated material management costs.